Achieving peaceful climate change adaptation through transformative governance. (November 2021) - Leonardsson, Hanna; Kronsell, Annica; Andersson, Erik; Burman, Anders; Blanes, Ruy; Da Costa, Karen; Hasselskog, Malin; Stepanova, Olga; Öjendal, Joakim
Highlights: In this article we ask how urgent climate change adaptation can be realised on the ground without furthering conflicts. We develop a theoretical framework on transparent and adaptive governance for peaceful climate change adaptation. We emphasise a learning methodology to cooperatively produce locally relevant and adaptive knowledge. We highlight the study of climate change adaptation in 'glocal' cross-border cases through a bottom-up approach. Taken together we propose a transformative governance approach vital for peaceful climate change adaptation. Abstract: Which form of governance is required to bridge tensions that stem from the urgent need of climate change adaptation (CCA) on the one hand, and the imperative of upholding peace and social stability in vulnerable areas on the other? This article proposes transformative governance as a framework and methodology for addressing this question. It recognizes that the increased pace of climate change requires urgent and thorough adjustments to actual or expected climate change effects through a transformation of societies to increase their capacity to build sustainability. Our framework for transformative governance approach responds to this imperative and is based on three components: a theoretical framework for peaceful CCA governance derived from the fields of sustainability governance, political ecology and peacebuilding, second, a 'glocal' and bottom-up approach illustrated by two examples of cross-border collaboration, that demonstrate peaceful CCA governance as necessarily glocal, thirdly a learning methodology that implies context-based, goal-oriented, pluralistic and interactive co-production of knowledge. These are argued to be vital conditions for implementing CCA governance that is transformative and supports peaceful societies.